Do overqualified employees hide knowledge? The mediating role of psychological contract breach - Zhang, Huiqin; Li, Linzhen; Shan, Xuanming; Chen, Anhang (Frontiers in Psychology, 2022)
Despite the negative effects of a sense of overqualification on organizations and individuals have been examined, it is debatable whether overqualified employees hide knowledge. Relying on the social comparison theory and psychological contract theory, this paper tried to investigate the non-linear relationship between perceived overqualification and knowledge hiding via psychological contract breach by surveying employees with bachelor’s degrees or above and eventually conducted 475 samples. The results indicated that psychological contract breach acts a partial mediating role in the inverted U-shaped relationship between perceived overqualification and knowledge hiding, while leader-member exchange acts as a moderator. The finding manifests that overqualification encourages employees to hide knowledge, but their possibly vigorous aspects will be displayed while a certain limit is exceeded. And it benefits to organizations for dialectically treating and properly placing overqualified employees and contributes to the researches on overqualified employees’ knowledge management by offering a new explanation and complete understanding of perceived overqualification and knowledge hiding, with peculiar eyes dedicated to psychology states of employees.